Ancient origin and high diversity of zymocin-like killer toxins in the budding yeast subphylum - Padraic G. Heneghan; Letal I. Salzberg; Eoin Ó Cinnéide; Jan A. Dewald; Christina E. Weinberg; Kenneth H. Wolfe (Proceedings of the National Academy of Sciences, 2025)
Zymocin is a well-characterized killer toxin secreted by some strains of the yeast Kluyveromyces lactis . It acts by cleaving a specific tRNA in sensitive recipient cells. Zymocin is encoded by a killer plasmid or virus-like element (VLE), which is a linear DNA molecule located in the cytosol. We hypothesized that a tRNA-cleaving toxin similar to zymocin may have caused the three parallel changes to the nuclear genetic code that occurred during yeast evolution, in which the codon CUG became translated as Ser or Ala instead of Leu. However, zymocin-like toxins are rare — both among species, and among strains within a species —and only four toxins of this type have previously been discovered. Here, we identified 45 zymocin-like toxin genes in Saccharomycotina, the budding yeast subphylum, using a bioinformatics strategy, and verified that many of them are toxic to Saccharomyces cerevisiae when expressed. Some of the toxin genes are located on cytosolic VLEs, whereas others are on VLE-derived DNA integrated into the nuclear genome. The toxins are extraordinarily diverse in sequence and show evidence of positive selection. Toxin genes were found in five taxonomic orders of budding yeasts, including two of the three orders that reassigned CUG codons, indicating that VLEs have been parasites of yeast species for at least 300 My and that their existence predates the genetic code changes.